KEARIFAN LOKAL MASYARAKT DALAM MENJAGA KELESTARIAN HUTAN TEMBAWANG DI DESA GURUNG MALAI KECAMATAN TEMPUNAK KABUPATEN SINTANG - Marianus, .; Lumangkun, Agustine; Wardenaar, Evy (JURNAL HUTAN LESTARI, 2017)
Local wisdom is a community's belief born form its ancestor which has positive value that has been assured from generation to generation and has become local culture. This research aims to find out the types of the local wisdom and to view the strategic actions in keeping that local wisdoms used by customary institutions. This research was conducted toward Dayak Seberuang tribe community of Gurung Mali village, Tempunak subdistrict, Sintang regency. The method used survey with SWOT analysis. The result of this research found that the local wisdoms of Gurung Mali village, Tempunak subdistrict, Sintang regency's community are: There is a belief toward Nabau (dragon) monster, sacred lands, mystical ladder and supernatural, and The very important roles of customary institutions in preserving local wisdom to always be held by the community. There are a few actions took by customary institutions in keeping the local wisdom such as; Coordinating to the community, implementing their duties based on their functions and understanding their customs explicitly. Meanwhile, the obstacles faced by customary institutions in preserving local wisdom are; The lack of indigenous people's knowledge towards customary sanctions. The lack of indigenous people's understanding towards land boundaries around the village. The lack of government's attention to conduct elucidation about Tembawang efficacy. From various strategic actions and the obstacles the customary institutions faced can be seen that the difference score between strength - effect and weakness - effect is 1,156 shows that Tembawang at Gurung Mali village has strength that; the customary institutions and the community coordinate to each other in preserving the sustainability of Tembawang. The difference score between opportunity - effect and threat - effect is 0,345 shows that Tembawang is potentially to become an ecotourism forest due to its sustainability and its wisdom.Keyword: Community, Customary institutions, forest, Local wisdom and Tembawang